The Effect of E-Booklet-Based Education on Preoperative Anxiety Among Patients Undergoing General Anesthesia at Queen Latifa General Hospital, Yogyakarta - Olivia, Shara Sthella; Purnamasari, Vita; Nugraheni, Cahaya (Sean Institute, 2025)
Preoperative anxiety is commonly experienced by patients before undergoing general anesthesia and can affect surgical outcomes. Approximately 80% of patients experience anxiety. Education using e-booklet media is expected to help reduce anxiety by providing clear information about the anesthesia procedure. To determine the effect of education using e-booklet media on the anxiety level of patients undergoing general anesthesia in the preoperative room at Queen Latifa General Hospital, Yogyakarta. This study used a quantitative approach with a quasi-experimental design, employing a one-group pre-test and post-test design. Respondents were patients undergoing surgery with general anesthesia for the first time. Data were collected using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire, completed before and after education via the e-booklet. Data analysis was performed using the Wilcoxon test. Before the intervention, most respondents experienced moderate to severe anxiety levels. After the intervention, the majority were at a low anxiety level. The Wilcoxon test showed a p-value of 0.001 (<0.005), indicating a significant difference in anxiety levels before and after the education. Education using e-booklet media has an effect on reducing the anxiety level of patients undergoing general anesthesia in the preoperative room. Hospitals are encouraged to implement the use of e-booklets as educational media for patients undergoing anesthesia procedures. Further research is recommended to explore the long-term effects and use more varied educational methods to enhance patient understanding.